OPHISTHOLEBES TETRODONTIS (TREMATODA : DIGENEA) A NEW RECORD FROM WALTAIR COAST - KRISHNA, P.V.; SREERAMULU, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
The host fish Tetrodon lunaris collected from Bay of Bengal of Visakhapatnam were examined for digenetic trematodes. A number of monogenetic and digenetic trematodes have been encountered. A digenean trematode Opistholebes tetrodontis has been reported for the first time from Waltair coast.